Pentecostal Prophets and the Ivorian Crisis: From Religious Performance to Ideological Struggle (Hekima Review, 2013)
Since the death of its first President in 1993, Côte d’Ivoire has been facing a political crisis whose climax was the post-electoral crisis of 2010-2011. Through-out this crisis, Pentecostal pastors prophesied about its outcome and also about the future of Côte d’Ivoire which, according to their insight, has a particular value in the eyes of God and should be led by a man of his choice who would defeat any spiritual or political coalition. The author of this article highlights the ideological nature of these religious performances and their affiliation to the nationalist movement embodied by the former president Laurent Gbagbo. Then he brings out the resistance to peace due to these “divine messages” and identifies two major challenges for the country: the necessity to work on perceptions and beliefs in other to achieve peace, and an urgent reflection on the way that religious movements should relate to the public sphere.